GAYA KOMUNIKASI APARATUR SIPIL NEGARA GENERASI Z DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI JAWA TIMUR - Zahroh Firdaus Taufik; Cucu Hayati (PUTRA JAWA PUBLISHER, 2023)
This research aims to analyze the communication style of Generation Z Civil Servants (ASN) within the Department of Labor and Transmigration in East Java Province, focusing on aspects of workplace culture such as decision-making approaches, communication styles, and character traits. This qualitative study adopts a post-positivist paradigm. The findings reveal that the communication style of Generation Z ASN members in the Department of Labor and Transmigration in East Java Province tends to prioritize collaborative decision-making and teamwork over individual work. They prefer to engage in discussions and exchange ideas within their teams, often referred to as